Silicon-Mediated Priming Induces Acclimation to Mild Water-Deficit Stress by Altering Physio-Biochemical Attributes in Wheat Plants - Hameed, Arruje; Farooq, Tahir; Hameed, Amjad; Sheikh, Munir Ahmad (Frontiers in Plant Science, 2021)
Water-deficit stress negatively affect seed germination, seedling development and plant growth by disrupting cellular and metabolic functions, reducing productivity and yield of field crops. In this study, sodium silicate (SS) has been employed as a seed priming agent for the acclimation of mild water-deficit stress by invoking priming memory in wheat plants. In pot experiments, the SS-primed (20, 40 and 60 mM) and non-primed control seeds were allowed to grow under normal and mild water-deficit conditions. Subsequently, known methods were followed for physiological and biochemical studies using flag leaves of 98-days mature wheat plants. The antioxidant and hydrolytic enzymes were upregulated while proteins, reducing sugars, total sugars, and glycine betaine increased significantly in flag leaves of wheat plants originated from SS-treated seeds compared to control under mild water-deficit stress. A significant decrease in MDA and proline contents suggested a controlled production of reactive oxygen species which resulted in enhanced cell membrane stability. The SS-priming induced a significant enhancement in yield, plant biomass, and 100-grains weight of wheat plants under water-deficit stress. The improvement in yield parameters indicated the induction of Si-mediated stress acclimation in SS-primed seeds which elicit water-deficit tolerance till the maturity of plants, ensuring sustainable productivity of climate-smart plants.